Implementation of Backpropagation ANN in Predicting Long Bean Crop Production in Sumatra Island Province - Zodi Martua Siallagan; Solikhun Solikhun (Trigin Publisher, 2022)
The production of long bean vegetable crops in Indonesia is very high, this is because this plant is easy to cultivate. Predicting the production of long bean vegetable crops on the island of Sumatra, where the data source comes from BPS (Central Bureau of Statistics). In predicting the use of ANN (Artificial Neural Networks) and the method used in this study is the backpropagation algorithm, this method will be used to predict or predict the production of long bean vegetable crops on the island of Sumatra. The results have been obtained using 4 models, namely the 6-5-1, 6-10-1, 6-15-1, and 6-20-1 models. Among the 4 existing models, the 6-5-1 model has the more accurate accuracy or the lowest error value with an MSE of 0.00711838.